Teaching Strategies Applied by PPL Teachers in Teaching Reading Comprehension - Dio Resta Permana (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
Permana, Dio R. 2015. Teaching Strategies Applied by PPL Teachers in Teaching Reading Comprehension. Thesis. English Education Study Program. Language and Art Department. Faculty of Education and Teacher Training. University Bengkulu. The research desribed the strategies applied by PPL teachers in teaching reading comprehension at SMA Negeri 5, SMA Negeri 1, and SMA Negeri 8 kota Bengkulu. This was a descriptive research. The subjects of this research were six PPL teachers who were divided into three different schools. The data were collected by using observation checklist and field notes. The data from observation checklist were identified, classified, and analyzed by using table of analysis. The field notes were included into the table of analysis. The result shows that the strategies applied by PPL teachers in pre-reading were introducing a topic, activating background knowledge, predicting, sharing existing knowledge, sequencing illustration, and set a purpose reading. In while-reading phase, there were reading aloud, skimming, scanning, rereading, and taking note. In post-reading phase, the strategies used by PPL teachers were summarizing, thinking critically, comprehension question, identifying the author’s purpose, examining grammatical structure, and follow-up writing exercise. In conclusion, there were sixteen strategies out of seventeen strategies applied by PPL teachers in teaching reading comprehension.